Novel Large Sulfur Bacteria in the Metagenomes of Groundwater-Fed Chemosynthetic Microbial Mats in the Lake Huron Basin - Sharrar, Allison M.; Flood, Beverly E.; Bailey, Jake V.; Jones, Daniel S.; Biddanda, Bopaiah A.; Ruberg, Steven A.; Marcus, Daniel N.; Dick, Gregory J. (Frontiers in Microbiology, 2017)
Little is known about large sulfur bacteria that inhabit sulfidic groundwater seeps in large lakes. To examine how geochemically relevant microbial metabolisms are partitioned among community members, we conducted metagenomic analysis of a chemosynthetic microbial mat in the Isolated Sinkhole, which is in a deep, aphotic environment of Lake Huron. For comparison, we also analyzed a white mat in an artesian fountain that is fed by groundwater similar to Isolated Sinkhole, but that sits in shallow water and is exposed to sunlight. De novo assembly and binning of metagenomic data from these two communities yielded near complete genomes and revealed representatives of two families of large sulfur bacteria. The Isolated Sinkhole community was dominated by novel members of the Beggiatoaceae that are phylogenetically intermediate between known freshwater and marine groups. Several of these Beggiatoacaeae had 16S rRNA genes that contained introns previously observed only in marine taxa. The Alpena fountain was dominated by populations closely related to Thiothrix lacustris and an SM1 euryarchaeon known to live symbiotically with Thiothrix spp. The SM1 genomic bin contained evidence of H2-based lithoautotrophy. Genomic bins of both the Thiothrix and Beggiatoacaeae contained genes for sulfur oxidation via the rDsr pathway, H2 oxidation via Ni-Fe hydrogenases, and the use of O2 and nitrate as electron acceptors. Mats at both sites also contained Deltaproteobacteria with genes for dissimilatory sulfate reduction (sat, apr, and dsr) and hydrogen oxidation (Ni-Fe hydrogenases). Overall, the microbial mats at the two sites held low-diversity microbial communities, displayed evidence of coupled sulfur cycling, and did not differ largely in their metabolic potentials, despite the environmental differences. These results show that groundwater-fed communities in an artesian fountain and in submerged sinkholes of Lake Huron are a rich source of novel large sulfur bacteria, associated heterotrophic and sulfate-reducing bacteria, and enigmatic archaea.